Impact of Helium-Oxygen Administered via High Velocity Nasal Insufflation on Delivery of Inhaled Nitric Oxide - Hertzog, James H.; Burr, Katlyn L.; Stump, Angela; Brown, Joel M.; Penfil, Scott; McMahon, Kimberly (Journal of Pediatric Intensive Care, 2020)
Inhaled nitric oxide (iNO) may be continued during the transition from invasive to noninvasive respiratory support. Upper airway obstruction from laryngeal edema following extubation and lower airway obstruction from asthma and bronchiolitis may be managed with inhaled helium. The coadministration of helium with iNO and the impact on delivered amounts of iNO have not been extensively studied. A bench model simulating a spontaneously breathing infant received iNO at varying preset doses delivered with either helium-oxygen or nitrogen-oxygen via a Vapotherm unit. iNO levels were measured at the simulated trachea. Results from the two conditions were compared using t-tests. When nitrogen-oxygen was used, there was no difference between preset and measured iNO levels. A significant difference was present when helium-oxygen was used, with a 10-fold increase in measured iNO levels compared with preset values. The use of helium resulted in a significant increase in measured iNO at the level of the simulated trachea. Clinicians must be aware that iNO will not be delivered at prescribed doses when used with helium under the conditions used in this study.
Keywords: inhaled nitric oxide; high flow nasal cannula; high velocity nasal insufflation